Temperature-dependent magnetic susceptibility behaviour of spinelloid and spinel solid solutions in the systems Fe2SiO4-Fe3O4 and (Fe,Mg)2SiO4-Fe3O4 - Kontny, Agnes; Woodland, Alan B.; Koch, Mario (Physics and chemistry of minerals, 2004)
The magnetic behaviour and Curie temperatures (TC) of spinelloids and spinels in the Fe3O4-Fe2SiO4 and Fe3O4-(Mg,Fe)2SiO4 systems have been determined from magnetic susceptibility (k) measurements in the temperature range −192 to 700 °C. Spinelloid II is ferrimagnetic at room temperature and the k measurements display a characteristic asymmetric hump before reaching a TCat 190 °C. Spinelloid V from the Mg-free system is paramagnetic at room temperature and hysteresis loops at various low temperatures indicate a ferri- to superparamagnetic transition before reaching the TC. The TCshows a non-linear variation with composition between −50 and −183 °C with decreasing magnetite component (XFe3O4). The substitution of Mg in spinelloid V further decreases TC. Spinelloid III is paramagnetic over nearly the total temperature range. Ferrimagnetic models for spinelloid II and spinelloid V are proposed. The TCof Fe3O4-Fe2SiO4 spinel solid solutions gradually decrease with increasing Si content. Spinel is ferrimagnetic at least to a composition of XFe3O4=0.20, constraining a ferrimagnetic to antiferromagnetic transition to occur at a composition of XFe3O4<0.20. A contribution of the studied ferrimagnetic phases for crustal anomalies on the Earth can be excluded because they lose their magnetization at relatively low temperatures. However, their relevance for magnetic anomalies on other planets (Mars?), where these high-pressure Fe-rich minerals could survive their exhumation or were formed by impacts, has to be considered.
Falsche Namensform in der Autorenbeschreibung. Richtig: Woodland, Alan B
Im Titel sind die Ziffern "2", "3" und "4" tiefgestellt
Gesehen am 24.09.2020